Building Community in the HIV Online Intervention Space: Lessons From the HealthMPowerment Intervention. (October 2021) - Blackburn, Natalie A.; Dong, Willa; Threats, Megan; Barry, Megan; LeGrand, Sara; Hightow-Weidman, Lisa B.; Soni, Karina; Pulley, Deren V.; Bauermeister, Jose A.; Muessig, Kate
Background: Mobile health platforms can facilitate social support and address HIV (human immunodeficiency virus) stigma but pose challenges for intervention design and participant engagement. Giddens's structuration theory, that individuals are shaped by—and shape—their communities through rules and resources that give them power to operate within these environments, provides a useful analytic framework for exploring these dynamic intervention spaces. Method: Data were drawn from an online randomized controlled trial intervention (HealthMpowerment) for young Black men who have sex with men to reduce condomless anal intercourse. We applied a conversational analysis informed by structuration theory to 65 user-generated conversations that included stigma content. We aimed to understand how the interdependent relationship between the intervention space and participants' contributions might contribute to behavior change. Results: Thirty five intervention participants contributed to the analyzed conversations. Our analysis identified three types of conversational processes that may underlie behavior change: (1) Through intervention engagement, participants established norms and expectations that shaped their discussions; (2) participants used anecdotes and anonymity to reinforce norms; and (3) intervention staff members sought to improve engagement and build knowledge by initiating discussions and correcting misinformation, thus playing an integral role in the online community. Conclusions: The lens of structuration theory usefully reveals potential behavior change mechanisms within the social interactions of an online intervention. Future design of these interventions to address HIV stigma should explicitly characterize the context in which individuals (study staff and participants) engage with one another in order to assess whether these processes are associated with improved intervention outcomes.